ANALYSIS OF FACTORS RELATED TO MOTHER'S CHARACTERISTICS AND MEASLES CASES IN CHILDREN AT SUBULUSSALAM CITY HOSPITAL IN 2022 - Silvia Arnisa; Darmawan; Susy Sriwahyuni; Danvil Nabela (RADJA PUBLIKA, 2023)
Measles is a disease that can be transmitted and is often experienced by children aged 5-13 years. The high rate of cases was 93 people who experienced measles in children in the child inpatient room at Subulussalam City Hospital. Measles is a paramyxoviridae group that enters the human body and then the virus will settle, multiply and can cause measles in children. Factors related to the incidence of measles in children are not immunized against measles, unhealthy homes, lack of mother's knowledge. This research was conducted aiming to analyze the factors related to the characteristics of the mother with the incidence of measles in children at Subulussalam City Hospital. This research method uses a quantitative descriptive analytic method with a cross sectional design through interview techniques using a questionnaire with 40 respondents. Based on the results of the independent variables that the age of the mother with the incidence of measles produces a P-value (0.017), education P-value (0.071), knowledge P-value (0.071), income P-value (0.896). The conclusion from the results the researchers have done at Subulussalam City Hospital can conclude that from the results of the P-value below <0.05 which is significant indicating that there is a relationship between several variables of maternal characteristics and the incidence of measles in children who have been tested based on univariate analysis and bivariate analysis .